Application of a Duration Model in Programs for Prevention of University Attrition - Verónica Herrero; Aldo Merlino; Silvia Ayllón; Gabriel Escanés (Universidad Autónoma de Baja California, 2013)
Institutional practices related to the prevention of desertion of university students increasingly require validated instruments in order to anticipate such behavior. In this regard, different statistical models generated from information related to the students themselves, their homes, their academic performance, among other determinants have demonstrated to be of crucial value. This study aims to demonstrate the importance of a series of determinants explored in other studies. The main objective is to apply a dropout rate predictive model with at risk university students in order to generate early and progressively more effective results. The research demonstrates the usefulness of the duration models in a sample of classroom students and the capacity to anticipate behavior of permanence/attrition across time. This was done with risk estimates using the Cox model.